Implementasi Pembelajaran Khot Naskhi dan Riq’ah di Mahad Umar bin Al-Khattab Putri Sidoarjo - Rohmah, Maidatur; Anwar, Najih (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
Khot is a method used to increase the maharoh of the book. Maharoh kitabah in learning Arabic must be considered for Arabic language educational institutions. Naskhi and riq''ah khot are types of khot which are implemented in learning at Ma'had Umar bin Al-Khattab Putri Sidoarjo. This study aims to determine the implementation of learning khot naskhi and riq''ah, supporting and inhibiting factors and solutions at Ma'had Umar bin Al-Khattab Putri Sidoarjo. This study uses a qualitative method. As for data collection techniques using interviews, observation, and documentation. The research subjects were the Khot teachers and first mustawa students. The results of the study can be concluded that the implementation of khot learning consists of three stages, namely planning, implementation, and evaluation. Supporters of the implementation of khot naskhi and riq'ah learning include a clean and comfortable environment as well as Arabic-speaking higher education institutions. The inhibiting factors include the different backgrounds of female students, the different writing equipment for khot, the paper used is too thin, and the teacher's explanation regarding how to write is lacking. Solutions to inhibiting the implementation of khot learning are giving examples gradually and slowly accompanied by explanations, aligning writing instruments, setting the use of thick paper, and teachers need to improve learning methods that can attract students.